GEOMETRICAL KNOWLEDGE LEVEL ACCORDING TO VAN HIELE’S MODEL - Silva Xavier, Eliandra (2021)
Considering that the appropriation of geometric knowledge can help the student to understand the world around him, this work aims to show how the teacher can analyze his student's level of geometric knowledge. As a theoretical contribution, using the Van Hiele Theory which considers that the appropriation of geometric knowledge occurs at five levels, level 1 (recognition, comparison and nomenclature of geometric figures by their appearance), level 2 (analysis of figures, properties and use of them ), level 3 (precise definitions, informal logical arguments and ordering of classes of geometric figures), level 4 (demonstrations and recognition of necessary and sufficient conditions) and level 5 (formal demonstration, establishment of theorems in different systems and comparison of them) .